General health of clinical psychologists in Scotland: its relationship to experienced stressors, professional and social support, and ways of coping - Burley, Adam George Weston (The University of Edinburgh, 2001)
The experience of stress by an individual can be conceptualised as a complex biopsychosocial response that results from interactions between life stressors, the individuals personal and environmental resources, and his or her cognitive appraisals and coping styles. Stress can manifest itself in varied ways in an individual, of which anxiety and affective disorders are the primary pathological representations (Friedman, Clark, and Gershon, 1992). The presence of support from other individuals has been described as one such resource which can alter the relationship between stressor and amount of stress experienced by an individual (Cassell, 1976). Similarly the method of coping an individual adopts in the face of stressors has been shown to have an impact upon how that stressor is experienced (Lazarus, 2001). Stress in mental health workers is an important area to study for a number of reasons including the negative impact it can have on patients care, the sufferer themselves, and the public's impression of mental health services in general. It has also been argued that mental health professionals may be more prone to experiencing stress as a result of working in human services. There is a growing body of evidence suggesting that clinical psychologists do experience high levels of work related stress, and that this stress is related to the amount of social support they perceive themselves to have (Cushway, Tyler, and Nolan, 1996). This study aimed to explore the relationships between the well being of clinical psychologists, the stressors they face in their work, and the support they receive in the face of those stressors. Data was collected from 180 clinical psychologists working in Scotland through self completed questionnaires via a postal survey. Questionnaires were chosen to measure demographic data, experience of life and work stressors, social and professional support, ways of coping, and general health. The associations between these measures are examined with a particular emphasis upon the relationships between the health outcome measure, and the other measured variables. The relationship of experienced stressors and general health to a range of demographic variables is also measured. Results are discussed in relation to previous research findings, and conclusions drawn relating to the findings of the study.
The general health of clinical psychologists in Scotland: its relationship to experienced stressors, professional and social support, and ways of coping